SISTEM PEMANTAUAN DAN KONTROL OTOMATIS KUALITAS AIR BERBASIS INTERNET OF THINGS (IOT) MENGGUNAKAN PLATFORM NODE-RED UNTUK BUDIDAYA UDANG - Ahmad Rifa'i; M Udin Harun Al Rasyid; Agus Indra Gunawan (P3M Politeknik Negeri Indramayu, 2021)
Water quality in shrimp farming is an important factor that needs attention. Therefore good water quality becomes a measure of the success rate of shrimp cultivation. The main problem is the poor quality of water during the maintenance period. To overcome this problem, this paper proposes to use an Internet of things (IoT) device that can monitor water quality conditions and take preventive measures in the form of early notification and automatic control of each actuator in the cultivation pond. Some of the sensors used are Dissolved Oxygen (DO), Hydrogen Potential (pH), Turbidity, Water temperature and water level (ultrasonic sensor). Furthermore, water quality data will be sent to the server (Node-Red Platform) using the MQTT (Message Queue Telemetry Transport) protocol communication. Data processing carried out on the server uses the IFTTT (If This Then That) method and produces a decision in the form of a command (command set) to control the actuator on the actuator control node. From the performance test results, the delay occurs in sending data from the publisher to the subscriber is an average of 260 ms using the public HIVEMQ Broker. Whereas in automatic control testing, the response graph shows the action taken by the actuator control device after getting the command set generated by the IFTTT method on the Node-Red platform.